Progress in non-fullerene acceptor based organic solar cells - Duan, L.; Elumalai, Naveen Kumar; Zhang, Y.; Uddin, A. (Elsevier BV * North-Holland, 2019)
Organic solar cells (OSCs) based on fullerene acceptors demonstrated significant growth over the past two decades with power conversion efficiencies (PCE) exceeding 13%. However, the advent of non-fullerene (NF) acceptors with superior optoelectronic properties, tunable morphology, and absorption characteristics, have resulted in a scenario where the NF OSCs have demonstrated higher PCE of over 14% in single junction and over 17% in tandem OSCs incorporating NF OSCs which is relatively higher than conventional fullerene-based counterparts. In this review, recent progress and advancements made in the field of NF OSCs is discussed and its photovoltaic device performance ranging across several donor: acceptor (D/A) combinations is elaborated. The advantages of each NF materials in conjunction with the donor molecules is deliberated in the context of D/A blends correlating it to device performance. In addition, the challenges in the development and application of NF OSCs are also discussed, providing an overview for future developments.